E.L.E.C. EUROPEAN LEAGUE FOR ECONOMIC COOPERATION (CYPRUS) LTD (E.L.E.C. CYPRUS) - (:unkn) unknown (My University, 2026)
Cyprus has been invited to join other European countries as members of E.L.E.C. the European League for Economic Cooperation, a Europe wide group of successful , distinguished personalities, interested in promoting the European Project through improving the functioning of the EU. The Founding members of E.L.E.C. Cyprus have identified a total of 50 Cypriots to invite them to join as the first members. I am pleased to invite you to join the group